Economic freedom between unbounded capitalism and Socialist denial and Islam’s position on it – descriptive theoretical study - Marif, Khalil Ahmed (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aims to highlight the role of the Islamic system in economic freedom and its success over the capitalist system, and a socialist in freedom. And between the pros and cons and the way of freedom in the mentioned systems. He emphasized that economic freedom in the capitalist system is absolute, there is no limit in it, but a little, while denying public ownership only an exception to the original, And the state’s non-interference in economic and financial activities. And with the denial of economic freedom in the socialist economic system and direct and absolute interference of the state in all economic and financial activities through the central planning system, With the recognition of private ownership, an exception to the original. The research emphasized that economic freedom in the Islamic economic system is neither absolute nor denied, Rather, a compromise between the two sects recognizes economic freedom, but within a limited scope, Because it is disciplined by the legal controls that are valid for all societies. And on the research methodology: I used it in the research as a theoretical and descriptive study that shows freedom in the prevailing economic doctrines with an explanation of Islam’s position on its restricted freedom and the importance of legitimate controls valid for humanity. The results were obtained and the most important ones are Economic freedom in the capitalist economic system is absolute without any control, and Economic freedom is denied in the socialist economic system, therefore Many criticisms of the capitalist and socialist economic system appeared throughout their history as a result of some wrong ideas on which the Philosophy of the two doctrines, however The right to analyze and prohibit is not anyone’s right but God alone, but the Economic freedom in the Islamic system is defined by Shari’a controls and constrained by restrictions that refer to the interests of the human community in general, though Islam’s mediation in economic freedom is between capitalist launch and socialist exile. One of the most important recommendations in this research Taking care of teaching Islamic economics in colleges and institutes, Commitment to economic freedom disciplined by Sharia controls, in order to eliminate corruption and bring human interests, and Following to this rule: every action is permissible unless there is evidence that it is prohibited.